2011
DOI: 10.1186/1743-422x-8-239
|View full text |Cite
|
Sign up to set email alerts
|

Human bocavirus (HBoV) in children with respiratory tract infection by enzyme linked immunosorbent assay (ELISA) and qualitative polymerase chain reaction (PCR)

Abstract: BackgroundHuman bocavirus (HBoV) is a recently discovered parvovirus associated with mild to severe lower respiratory tract infections in children, the aim of the work was determination of human bocavirus in nasopharyngeal aspirate (NPA) of infants by qualitative PCR and determination of acute human bocavirus infection by estimation of immunoglobulin M (IgM) antibodies in serum by enzyme linked immunosorbent assay.ResultsTwenty two (22%) out of the 100 NPA specimens of the patients with respiratory manifestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
18
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 26 publications
5
18
1
Order By: Relevance
“…We estimated HBoV IgM as another diagnostic tool for diagnosis of HBoV causing ALRI and we found that there were13/ 123 (16%) positive cases by ELISA, these results were in agreement with previous results of IgM detection in children with HBoV in the studies by Zaghloul (2011) andSöderlund-Venermo et al, (2009) that were 18%, 19% respectively.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…We estimated HBoV IgM as another diagnostic tool for diagnosis of HBoV causing ALRI and we found that there were13/ 123 (16%) positive cases by ELISA, these results were in agreement with previous results of IgM detection in children with HBoV in the studies by Zaghloul (2011) andSöderlund-Venermo et al, (2009) that were 18%, 19% respectively.…”
Section: Resultssupporting
confidence: 82%
“…This study result was in agreement with that of Zaghloul (2011). However, our results were higher than that of Lindner et al, (2008) There was significant association between high viral load and positive serology that probably indicate active HBoV infection; there were 13IgM-positive serum samples of patients who had high viral load among 16 IgM-positive serums.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…To increase sensitivity of virus detection by ELISA, sprouts from tubers have been used (Mumford et al, 2000). Conventional polymerase chain reaction (PCR) or reverse transcription-PCR (RT-PCR) which have high sensitivity and specificity over ELISA-based methods and have been used to detect DNA viruses or RNA viruses, respectively (Bostan and Peker, 2009;Stark et al, 2008;Zaghloul, 2011). RT-PCR and immunocapture reverse transcription polymerase chain reaction (IC-RT-PCR) have been employed for detection of PLRV in plant or in aphid vectors (Ahouee et al, 2010;Hadidi et al, 1993;Peiman and Xie, 2006;Singh et al, 1995;1997).…”
mentioning
confidence: 99%